Economics integration and cooperating in Borneo towards sustainable economic development: towards poverty eradication - Kasim Md Mansur; Sidah Idris (Lahore : The Economics and Social Development Organization, 2016)
Purpose: This paper discusses the challenges and prospects of economic development of Malaysia specifically Sabah within Borneo Economic Community including Brunei Darussalam and Kalimantan Indonesia. Free trade is a significant stimulus to regional production, linkages and competitiveness. Borneo region has made significant progress in that regard since the implementation of the ASEAN Free Trade Area (AFTA) from 1993 as well as BIMP-EAGA. The AFTA BIMP-EAGA initiative has been particularly successful in reducing tariffs and other trade rules and regulation among member countries in the trade in goods including labor mobility. However, regional free trade alone is not sufficient to release the full energies and the inherent potential of Malaysia within Borneo region. Deeper economic integration is necessary for Borneo to cope effectively with the unprecedented opportunities as well as the unprecedented challenges, on both scale and depth, unleashed by globalization. China and India have altered the global economic landscape through huge market openings and greater competition. Methodology: Meanwhile, interlinked supply networks have proliferated all over the world, among many other innovative and more efficient ways in value creation and industrial organization. Other factors are related to movements of new ideas, people and resources across national boundaries. Findings: Henceforth, Malaysia in particular and other countries located in Borneo in general has to be transformed into a stable, prosperous, and highly competitive region with equitable economic development, and reduced poverty and socio-economic disparities. As such, the economic collaboration will empower Borneo to remain a dynamic and competitive player in the regional and global supply chains. But the same process is also predicated on wide-ranging adjustments and reforms to be carried out by Governments and the business sectors, among other stakeholders in the region. Malaysia vis a vis Borneo has three key strengths in the economic arena. Malaysia endowed with abundant natural resources. Recommendations: The region also has large supplies of professionals and talented people and has the capability to adopt, adapt and advance technology. By leveraging on these strengths Borneo economic development is likely to be realized sooner than later.